Pengaruh Senam Zumba Terhadap Waist Circumference Pada Wanita Obesitas Di Sanggar Senam Rm7 - Susanti, Eva, Dwi Rosella Komala Sari, SSt.FT.,M.Fis (2017)
Background: Flab (obesity) Generally, obesity is very dangerous for human life but the most dangerous obesity lies in abdominal because in the abdominal area there are organs which are essential for the body, so if there are disruption it will cause metabolic syndrome disease. Generally, obesity in the abdominal area is called central obesity. waist circumstance is an index to measure central obesity. Zumba dance is kind of exercise to burn the fat, especially in abdominal fat. It causes Zumba dance movement focuses on waist and hips. Objective: To know the impact of Zumba dance toward waist circumstance for women obese in RM7 gymnasium. Methods: The type of this research is quasi-experimental with pre and post test of control group design, namely the sample of the treatment group was given exercises of Zumba dance for 4 weeks with a frequency of three times a week, 65%-75% exercise intensity, and 60 minutes for exercise. While the sample of the control group was not given exercise. Measurements of waist circumstance were done by midline. The technique of analysis data using Wilcoxon test to test the effect and Mann-Whitney test to test the different effect. Results: After statistic test was done by using Wilcoxon test for treatment group, the result is p = 0,002 which means that there is impact of Zumba dance toward waist circumstance for women obese in RM7 gymnasium and the result of the control group is p = 0,343 which means that there are not impact. After statistic test was done by using Mann Whitney test, the result is p = 0,000 which means that there is a different impact. Conclusion: There is impact of Zumba dance toward waist circumstance for women obese in RM7 gymnasium.